2020
DOI: 10.1016/j.ejvs.2020.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Is it Possible to Safely Maintain a Regular Vascular Practice During the COVID-19 Pandemic?

Abstract: This paper evaluates the protocol adopted during the emergency phase of the COVID-19 pandemic to maintain elective activity in a vascular surgery unit while minimising the risk of contamination to both patients and physicians. All elective patients were submitted to nasopharyngeal swabs; all emergency patients were considered as possibly contaminated, in order to minimise contamination possibilities to other patients and hospital professionals. This approach should be considered in an emergency situation in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 6 publications
1
25
1
Order By: Relevance
“…Recently, Pini et al reported the results of vascular surgical activity in the Bologna metropolitan area between 8 March and 8 April 2020. 19 Among 34 patients treated in the acute/ emergency setting, only two were operated on for ALI (one being positive to SARS-CoV-2), a number even lower than the same period in 2019. However, in that series, COVID-19 affected only 3.9% of patients (6/152), whereas in another experience COVID-19 was present in 21% of patients (64/ 305).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Pini et al reported the results of vascular surgical activity in the Bologna metropolitan area between 8 March and 8 April 2020. 19 Among 34 patients treated in the acute/ emergency setting, only two were operated on for ALI (one being positive to SARS-CoV-2), a number even lower than the same period in 2019. However, in that series, COVID-19 affected only 3.9% of patients (6/152), whereas in another experience COVID-19 was present in 21% of patients (64/ 305).…”
Section: Discussionmentioning
confidence: 98%
“…The establishment of a strict emergency protocol allowed the continuation of vascular surgery activity during the COVID-19 pandemic outbreak, as underlined by the experience of some highvolume center for vascular pathology in northern Italy. [10][11][12] Despite this, 1 patient developed fever and respiratory symptoms during the postoperative hospital stay and tested positive for COVID-19 at the NPS. After the patient's transfer to the dedicated Unit, we continued to apply the same emergency protocol since no one among the other inpatients or our staff members were found positive at the NPS or developed symptoms suggestive for COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…4,9e14 Only a few months later, the world faced a second pandemic wave, and numerous questions remained unanswered ahead of this challenge. 15,16 Because of the complex multimorbidity of patients with cardiovascular and cerebrovascular emergencies, these patients are known to be at particular risk of a SARS-CoV-2 infection and unfavourable outcomes. 17 The current study used large, updated health insurance claims data and additional information on confirmed SARS-CoV-2 infection status to further illuminate the impact of COVID-19 on in hospital mortality.…”
Section: Introductionmentioning
confidence: 99%